A note on artificial weathering of spruce (Picea abies) with a carbonised layer. (3rd April 2018) - Kampe, Anja; Pfriem, Alexander
ABSTRACT: Wood in outdoor applications undergoes various degradation processes such as biological degradation as well as weathering. However, since carbon black is a very effective photostabilizer, it is hypothesised that wood surfaces can be protected from weathering by a layer of carbon (charcoal). Norway spruce ( Picea abies ) samples were pyrolised to create carbonised layers of varying thickness and exposed to artificial weathering for eight weeks. To investigate surface changes due to weathering, colour measurements and ATR FTIR measurements were made. The results show that carbonised surfaces protect wood from weathering but they also undergo chemical changes. Thus, the thickness of carbonised layers influences the weathering protection of wood.